A Study on Chromosomal Aberrations in Peripheral Blood Immune Cells of Medical Radiation Diagnostics Practitioners Exposed to Occupational Radiation - Gao, Yichen (International Journal of Public Health and Medical Research, 2025)
Objective: To investigate the health effects of radiation exposure among medical radiation diagnostics practitioners. Methods: A total of 1125 medical radiation diagnostics workers who underwent occupational health examinations between 2023 and 2024 were selected as the study subjects. They were categorized into groups based on gender, age, and length of service. Differences in white blood cell count, platelet count, and chromosomal aberration rates among the groups were analyzed. Logistic regression was used to identify factors influencing the rate of chromosomal aberrations. Results: Among the 1125 workers, 684 (60.8%) were male and 441 (39.2%) were female. The non-aberration group comprised 1060 individuals (94.2%), with a mean radiation exposure duration of 6.85 ± 8.137 years and a mean age of (33.17 ± 10.420) years. The chromosomal aberration group included 65 individuals (5.8%). Radiation exposure time and age were identified as influencing factors for chromosomal aberrations in radiation workers (P < 0.05). For each additional year of radiation exposure, the risk of chromosomal aberrations increased by 3.9% (OR = 1.039, 95% C.I. 1.013-1.067). Conclusion: Long-term, low-dose ionizing radiation exposure leads to an increased incidence of chromosomal aberrations. Enhanced monitoring and improved radiation protection for medical radiation practitioners are recommended.